Machiavellian Personality, Commitment, and Self-Efficacy: Unraveling Whistleblowing Intentions in Accounting Students: Kepribadian Machiavellian, Komitmen, dan Efikasi Diri: Mengungkap Niat Melakukan Whistleblowing pada Mahasiswa Akuntansi - Azmiyanti, Rizdina; Suhartini, Dwi; Yunida Putri, Sofie (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the relationship between commitment professionalism, Machiavellian personality, and whistleblowing intentions among accounting students, while examining self-efficacy as a moderating variable. Conducted on a sample of 200 7th-semester accounting students at Universitas Pembangunan Nasional